1972
DOI: 10.3181/00379727-140-36674
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone and Corticosterone Administration to Pregnant Rats: Effects on Pituitary-Adrenocortical Function in the Newborn

Abstract: Although there is convincing evidence that the fetal pituitary-adrenocortical system of the rat is fully operative in late stages of gestation, the question of whether maternal corticosteroids traverse the placenta to influence fetal hypophyseal function has not been satisfactorily resolved. Enlargement of the fetal adrenal occurs if pregnant rats are either adrenalectomized (1-3) or treated with adrenocortical inhibitors (4, 5). Administration of cortisone to either intact or adrenalectomized pregnant rats ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1976
1976
1991
1991

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…After Day 18, however, corticosterone concentrations in the maternal circulation were directly related to the conceptus number (Dupouy et al, 1975) It has been reported that the fetus participates in the regulation of luteal function (Kittinger et al, 1980). In the present study, ACTH treatment reduced the weights of the fetus and placenta (Table 1), which confirmed the previous report for mice (Paul & D'Angelo, 1972). There are several reports that adrenalectomy or corticoid treatment of the mother affect fetal adrenal function (Knobil & Briggs, 1954;Baldwin, 1979).…”
Section: Introductionsupporting
confidence: 82%
“…After Day 18, however, corticosterone concentrations in the maternal circulation were directly related to the conceptus number (Dupouy et al, 1975) It has been reported that the fetus participates in the regulation of luteal function (Kittinger et al, 1980). In the present study, ACTH treatment reduced the weights of the fetus and placenta (Table 1), which confirmed the previous report for mice (Paul & D'Angelo, 1972). There are several reports that adrenalectomy or corticoid treatment of the mother affect fetal adrenal function (Knobil & Briggs, 1954;Baldwin, 1979).…”
Section: Introductionsupporting
confidence: 82%
“…Physiological levels of exogenously administered corticosterone have been shown to inhibit the sub¬ sequent pituitary-adrenal response to stress in adult rats (Zimmerman & Critchlow 1969;Jones & Tiptaft 1977) and feedback inhibition of ACTH by corticosteroids also appears to occur in the perina¬ tal period (Paul & D'Angelo 1972;Milkovié et al 1976). However, studies of feedback inhibition during the period between weaning and puberty have yielded conflicting results.…”
mentioning
confidence: 96%